VOC (volatile organic compound) improved filler as well as preparation method and application thereof

By preparing and adding VOC to improve fillers, the problem of VOC release of thermoplastic resins during processing is solved, significantly improving its VOC performance and expanding its application range.

CN119701875APending Publication Date: 2025-03-28HEFEI GENIUS NEW MATERIALS CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202311269955.2
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2023-09-28
Publication Date
2025-03-28

AI Technical Summary

Technical Problem

Volatile organic compounds (VOCs) produced by thermoplastic resins during processing are harmful to human health and the environment, limiting their application in certain fields.

Method used

A method of preparing VOC improved filler is adopted to prepare mesoporous hydroxylated nickel oxide by mixing nickel chloride, template agent, oxidizing agent, sodium hydroxide and deionized water, and then combined with dimethylbisoctadecyl ammonium bromide and other substances to form a modified mesoporous hydroxylated nickel oxide filler to adsorb small molecular substances in the air.

Benefits of technology

It significantly improves the VOC performance of thermoplastic resins, effectively adsorbs small molecular substances such as formaldehyde, acetaldehyde, etc., reduces the release of VOC, and expands the application range of thermoplastic resin composite materials.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0004475281330000051
    Figure BDA0004475281330000051
  • Figure BDA0004475281330000061
    Figure BDA0004475281330000061
Patent Text Reader

Abstract

The invention discloses a VOC improved filler and a preparation method and application thereof.The preparation method comprises the steps that nickel chloride, a template agent, an oxidizing agent, sodium hydroxide and deionized water are mixed and react for 5-7 h at the temperature of 30-50 DEG C, and mesoporous hydroxylated nickel oxide is prepared; mixing the mesoporous hydroxylated nickel oxide with dimethyl dioctadecyl ammonium bromide, absolute ethyl alcohol and deionized water, and reacting at 40-60 DEG C for 6-10 hours to obtain a mixed solution; and filtering, washing and drying the mixed solution to obtain the VOC improved filler, namely the dimethyl dioctadecyl ammonium bromide modified mesoporous hydroxylated nickel oxide filler. The VOC improved filler can remarkably improve the performance of adsorbing small-molecule chemical substances, so that the VOC performance of a thermoplastic resin composite material is improved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of functional fillers, and specifically relates to a preparation method of a VOC improved filler and the VOC improved filler, and also relates to a thermoplastic resin composite material containing the VOC improved filler and a preparation method thereof. Background Art

[0002] VOC is the abbreviation of volatile organic compounds. Usually, VOC refers to a class of active volatile organic compounds, that is, the kind of volatile organic compounds that can cause harm. This type of volatile organic compounds has a huge impact on human health. When it reaches a certain concentration, people will feel headaches, nausea, vomiting, fatigue, etc. in a short period of time. In severe cases, convulsions and coma will occur. It will also damage the liver, kidneys, brain and nervous system of people, causing serious consequences such as memory loss.

[0003] Plastic is a common material for products in our daily life. The most common process in its production and processing is injection molding. Injection molding is to inject molten plastic into the plastic product mold under pressure, and then cool and mold it to obtain the desired plastic parts. Injection molding waste gas is generated during the heating and molding process. Thermoplastic resin is a widely used polymer polyester resin, but its VOC release limits its application in some specific fields. Summary of the invention

[0004] In view of this, it is necessary for the present invention to provide a method for preparing a VOC improved filler, by which a VOC improved filler capable of better improving the VOC performance of a thermoplastic resin can be prepared.

[0005] In order to achieve the above object, the present invention adopts the following technical solutions:

[0006] The first aspect of the present invention provides a method for preparing a VOC improved filler, comprising the following steps:

[0007] Mix nickel chloride, template, oxidant, sodium hydroxide and deionized water, and react at 30-50° C. for 5-7 hours to prepare mesoporous hydroxylated nickel oxide;

[0008] The mesoporous hydroxylated nickel oxide is mixed with dimethyl dioctadecyl ammonium bromide, anhydrous ethanol and deionized water, and reacted at 40-60° C. for 6-10 hours to obtain a mixed solution;

[0009] The mixed solution is filtered, washed and dried to obtain a VOC improved filler, namely a mesoporous hydroxylated nickel oxide filler modified by dimethyl dioctadecyl ammonium bromide.

[0010] In a further embodiment, the template agent is ethylenediamine.

[0011] In a further embodiment, the oxidant is hydrogen peroxide.

[0012] In a further embodiment, in the step of obtaining mesoporous hydroxylated nickel oxide, the mass ratio of nickel chloride, template, oxidant, sodium hydroxide and deionized water is (30-40): (16-18): (8-12): (28-32): (70-90).

[0013] In a further embodiment, in the step of obtaining a mixed solution, the mass ratio of the mesoporous hydroxylated nickel oxide, dimethyl dioctadecyl ammonium bromide, anhydrous ethanol and deionized water is (28-30):(4-6):(50-60):(80-100).

[0014] The second aspect of the present invention discloses a VOC improved filler, which is prepared by the preparation method described in the first aspect of the present invention.

[0015] The third aspect of the present invention provides use of the VOC-modifying filler according to the second aspect of the present invention in a thermoplastic resin composite material.

[0016] A fourth aspect of the present invention provides a thermoplastic resin composite material, which is prepared by weight of 95-115 parts of a thermoplastic resin, 8-12 parts of a VOC-improving filler as described in the second aspect of the present invention, and 0.1-0.5 parts of an antioxidant;

[0017] In a further embodiment, the thermoplastic resin is selected from one of polyethylene (PE), polypropylene (PP), polyethylene terephthalate (PET), polybutylene terephthalate (PBT), and polyamide 6 (PA6).

[0018] In a further embodiment, the antioxidant is selected from at least one of tris(2,4-di-tert-butyl)phenyl phosphite (referred to as Irganox 168), pentaerythritol tetrakis[β-(3,5-di-tert-butyl-4-hydroxyphenyl)propionate (referred to as Irganox 1010) and 1,3,5-trimethyl-2,4,6-(3,5-di-tert-butyl-4-hydroxybenzyl)benzene (referred to as Irganox 1330).

[0019] A fifth aspect of the present invention provides a method for preparing the thermoplastic resin composite material as described in the fourth aspect of the present invention, comprising the following steps:

[0020] Weigh 95-115 parts of thermoplastic resin, 8-12 parts of VOC improved filler, and 0.1-0.5 parts of antioxidant according to the weight ratio, mix and stir evenly to obtain a mixture;

[0021] The mixed material is melt-extruded and granulated to obtain a thermoplastic resin composite material.

[0022] Beneficial effects of the present invention:

[0023] The VOC improved filler in the present invention, i.e., the mesoporous hydroxylated nickel oxide type VOC improved filler modified by dimethyl dioctadecyl ammonium bromide, can effectively adsorb small molecular substances in the air, such as formaldehyde, acetaldehyde, etc., thereby significantly improving the VOC performance of thermoplastic resins.

[0024] The present application first prepares mesoporous hydroxylated nickel oxide, and the specific reaction process is as follows:

[0025] Ni 2+ +2OH - →Ni(OH)2

[0026] 2Ni(OH)2+H2O2→2NiO(OH)+2H2O;

[0027] Subsequently, hydroxylated mesoporous nickel oxide was modified using dimethyldioctadecylammonium bromide. An interaction force was formed between the organic functional groups of dimethyldioctadecylammonium bromide and the surface hydroxyls of the mesoporous hydroxylated nickel oxide. The side chains and organic functional groups of dimethyldioctadecylammonium bromide were coated on the surface of the mesoporous hydroxylated nickel oxide to form a covering layer, thereby increasing the gap between effective adsorption molecules. Compared with mesoporous hydroxylated nickel oxide, the performance of adsorbing small molecule chemicals was significantly improved, thereby improving the VOC performance of thermoplastic resins. DETAILED DESCRIPTION

[0028] Embodiments of the present invention are described in detail below. The embodiments described below are exemplary and are only used to explain the present invention, and should not be construed as limiting the present invention.

[0029] Unless otherwise defined, all technical and scientific terms used herein have the same meaning as those generally understood by those skilled in the art of the present invention. The terms used herein in the specification of the present invention are only for the purpose of describing specific embodiments and are not intended to limit the present invention. In addition, unless otherwise specified, methods that do not specifically record conditions or steps are conventional methods, and the reagents and materials used can be obtained from commercial sources.

[0030] The specific information of each raw material used in the following examples and comparative examples is as follows:

[0031] PBT (model 2002U), Polyplastics, Japan; PP (model Z30S), Maoming Petrochemical; PE (model 5070), Panjin Ethylene; PA6 (model CM1017), Toray, Japan; PET (model 008L), Aclo, Canada; nickel chloride, Jinan Lebin Chemical Co., Ltd.; anhydrous ethanol, Shandong Taixi Chemical Co., Ltd.; ethylenediamine, Jinan Mingwei Chemical Co., Ltd.; hydrogen peroxide, Wuhan Mingqian Technology Co., Ltd.; sodium hydroxide, Shandong Zhengyu Chemical Technology Co., Ltd.; dimethyl dioctadecyl ammonium bromide, Hubei Watson Chemical Technology Co., Ltd.; deionized water, Xiamen Aoquan Environmental Protection Technology Co., Ltd.; antioxidants (models Irganox168, Irganox1010, Irganox1330), BASF.

[0032] Example 1

[0033] Preparation of VOC improved fillers

[0034] (1) Weigh 300 g of nickel chloride, 160 g of template agent ethylenediamine, 80 g of oxidant hydrogen peroxide, 280 g of sodium hydroxide, and 700 g of deionized water, place them in a reaction vessel, react at 30° C. for 5 h, filter, wash, and dry to obtain mesoporous hydroxylated nickel oxide;

[0035] (2) 280 g of mesoporous hydroxylated nickel oxide was mixed with 40 g of dimethyl dioctadecyl ammonium bromide, 500 g of anhydrous ethanol, and 800 g of deionized water, placed in a reaction vessel, and reacted at 40° C. for 6 h to obtain a mixed solution;

[0036] (3) The mixed solution is filtered, washed and dried to obtain the VOC improved filler M1.

[0037] Preparation of PP composite materials

[0038] (1) 95 parts of PP, 8 parts of VOC improved filler M1, and 0.1 parts of Irganox 1010 were weighed and mixed and stirred uniformly to obtain a mixture;

[0039] (2) extruding the mixture obtained in step (1) through a twin-screw extruder to form granules to obtain a PP composite material, which is denoted as P1;

[0040] Wherein, the twin-screw extruder includes six temperature zones arranged in sequence, the temperature of the first temperature zone is 170°C, the temperature of the second temperature zone is 230°C, the temperature of the third temperature zone is 230°C, the temperature of the fourth temperature zone is 230°C, the temperature of the fifth temperature zone is 230°C, the temperature of the sixth temperature zone is 230°C, the head temperature of the twin-screw extruder is 230°C, and the screw speed is 220r / min.

[0041] Comparative Example 1

[0042] This comparative example adopts the same implementation method as Example 1 to prepare the PP composite material, except that the VOC improved filler is replaced by the mesoporous hydroxylated nickel oxide prepared in Example 1. The other steps are the same as Example 1, and the specific steps are as follows:

[0043] (1) 95 parts of PP, 8 parts of the mesoporous hydroxylated nickel oxide prepared in Example 1, and 0.1 parts of Irganox 1010 were weighed and mixed and stirred to obtain a mixture;

[0044] (2) extruding the mixture obtained in step (1) through a twin-screw extruder to form granules to obtain a PP composite material, which is denoted as D1;

[0045] Wherein, the twin-screw extruder includes six temperature zones arranged in sequence, the temperature of the first temperature zone is 170°C, the temperature of the second temperature zone is 230°C, the temperature of the third temperature zone is 230°C, the temperature of the fourth temperature zone is 230°C, the temperature of the fifth temperature zone is 230°C, the temperature of the sixth temperature zone is 230°C, the head temperature of the twin-screw extruder is 230°C, and the screw speed is 220r / min.

[0046] The PP composite materials prepared in Example 1 and Comparative Example 1 were made into strips by injection molding to test VOC performance. The test results are shown in the following table:

[0047] Test items Test Standards unit P1 D1 benzene GB / T 27630 <![CDATA[μg / m 3 ]]> 41 71 Toluene GB / T 27630 <![CDATA[μg / m 3 ]]> 81 105 Ethylbenzene GB / T 27630 <![CDATA[μg / m 3 ]]> 91 136 Xylene GB / T 27630 <![CDATA[μg / m 3 ]]> 121 147 Styrene GB / T 27630 <![CDATA[μg / m 3 ]]> 23 38 formaldehyde GB / T 27630 <![CDATA[μg / m 3 ]]> 48 62 Acetaldehyde GB / T 27630 <![CDATA[μg / m 3 ]]> 19 31 Acrolein GB / T 27630 <![CDATA[μg / m 3 ]]> 7 15

[0048] It can be seen from the test results in the above table that the VOC performance of the PP composite material in Example 1 is significantly better than that in Comparative Example 1.

[0049] Example 2

[0050] Preparation of VOC improved fillers

[0051] (1) Weigh 400 g of nickel chloride, 180 g of template agent ethylenediamine, 120 g of oxidant hydrogen peroxide, 320 g of sodium hydroxide, and 900 g of deionized water, place them in a reaction vessel, react at 50° C. for 7 h, filter, wash, and dry to obtain mesoporous hydroxylated nickel oxide;

[0052] (2) 300 g of mesoporous hydroxylated nickel oxide was mixed with 60 g of dimethyl dioctadecyl ammonium bromide, 600 g of anhydrous ethanol, and 1.0 kg of deionized water, placed in a reaction vessel, and reacted at 60° C. for 10 h to obtain a mixed solution;

[0053] (3) Filtering, washing and drying the mixed solution to obtain VOC improved filler M2.

[0054] Preparation of PBT composite materials

[0055] (1) 115 parts of PBT, 12 parts of VOC improved filler M2, 0.1 parts of antioxidant Irganox 1010, 0.2 parts of antioxidant Irganox 168, and 0.2 parts of antioxidant Irganox 1330 were weighed and mixed and stirred to obtain a mixture;

[0056] (2) extruding the mixture obtained in step (1) through a twin-screw extruder to form granules to obtain a PBT composite material, which is denoted as P2;

[0057] Among them, the twin-screw extruder includes six temperature zones arranged in sequence, the temperature of the first temperature zone is 200°C, the temperature of the second temperature zone is 230°C, the temperature of the third temperature zone is 240°C, the temperature of the fourth temperature zone is 240°C, the temperature of the fifth temperature zone is 240°C, the temperature of the sixth temperature zone is 240°C, the head temperature of the twin-screw extruder is 240°C, and the screw speed is 300r / min.

[0058] Comparative Example 2

[0059] This comparative example adopts the same implementation method as Example 2 to prepare the PBT composite material, except that the VOC improved filler is replaced by the mesoporous hydroxylated nickel oxide prepared in Example 2; the rest is the same as Example 2, and the specific steps are as follows:

[0060] (1) 115 parts of PBT, 12 parts of the mesoporous hydroxylated nickel oxide prepared in Example 2, 0.1 parts of antioxidant Irganox 1010, 0.2 parts of antioxidant Irganox 168, and 0.2 parts of antioxidant Irganox 1330 were weighed and mixed and stirred to obtain a mixture;

[0061] (2) The mixed material obtained in step (1) is extruded and granulated from a twin-screw extruder to obtain a PBT composite material, which is recorded as D2.

[0062] Among them, the twin-screw extruder includes six temperature zones arranged in sequence, the temperature of the first temperature zone is 200°C, the temperature of the second temperature zone is 230°C, the temperature of the third temperature zone is 240°C, the temperature of the fourth temperature zone is 240°C, the temperature of the fifth temperature zone is 240°C, the temperature of the sixth temperature zone is 240°C, the head temperature of the twin-screw extruder is 240°C, and the screw speed is 300r / min.

[0063] The PBT composite materials prepared in Example 2 and Comparative Example 2 were made into strips by injection molding to test VOC performance. The test results are shown in the following table:

[0064]

[0065]

[0066] It can be seen from the test results in the above table that the VOC performance of the PBT composite material prepared in Example 2 is better than that of Comparative Example 2.

[0067] Example 3

[0068] Preparation of VOC improved fillers

[0069] (1) Weigh 350 g of nickel chloride, 170 g of template agent ethylenediamine, 100 g of oxidant hydrogen peroxide, 300 g of sodium hydroxide, and 800 g of deionized water, place them in a reaction vessel, react at 40° C. for 6 h, filter, wash, and dry to obtain mesoporous hydroxylated nickel oxide;

[0070] (2) 290 g of mesoporous hydroxylated nickel oxide was mixed with 50 g of dimethyl dioctadecyl ammonium bromide, 550 g of anhydrous ethanol, and 900 g of deionized water, placed in a reaction vessel, and reacted at 50° C. for 8 h to obtain a mixed solution;

[0071] (3) The mixed solution is filtered, washed and dried to obtain VOC improved filler M3.

[0072] Preparation of PE composite materials

[0073] (1) 105 parts of PE, 10 parts of VOC improved filler M3, 0.1 parts of antioxidant Irganox 168, and 0.2 parts of antioxidant Irganox 1010 were weighed and mixed and stirred to obtain a mixture;

[0074] (2) The mixed material obtained in step (1) is extruded and granulated from a twin-screw extruder to obtain a PE composite material, which is denoted as P3.

[0075] Among them, the twin-screw extruder includes six temperature zones arranged in sequence, the temperature of the first temperature zone is 120°C, the temperature of the second temperature zone is 180°C, the temperature of the third temperature zone is 180°C, the temperature of the fourth temperature zone is 180°C, the temperature of the fifth temperature zone is 180°C, the temperature of the sixth temperature zone is 180°C, the head temperature of the twin-screw extruder is 180°C, and the screw speed is 300r / min.

[0076] Comparative Example 3

[0077] This comparative example adopts the same implementation method as Example 3 to prepare the PE composite material, the only difference being that the VOC improved filler is replaced by the mesoporous hydroxylated nickel oxide prepared in Example 3; the other steps are the same as Example 3, and the specific steps are as follows:

[0078] (1) 105 parts of PE, 10 parts of the mesoporous hydroxylated nickel oxide prepared in Example 3, 0.1 parts of antioxidant Irganox 168, and 0.2 parts of antioxidant Irganox 1010 were weighed and mixed and stirred to obtain a mixture;

[0079] (2) The mixed material obtained in step (1) is extruded and granulated from a twin-screw extruder to obtain a PE composite material, which is recorded as D3.

[0080] Among them, the twin-screw extruder includes six temperature zones arranged in sequence, the temperature of the first temperature zone is 120°C, the temperature of the second temperature zone is 180°C, the temperature of the third temperature zone is 180°C, the temperature of the fourth temperature zone is 180°C, the temperature of the fifth temperature zone is 180°C, the temperature of the sixth temperature zone is 180°C, the head temperature of the twin-screw extruder is 180°C, and the screw speed is 300r / min.

[0081] The PE composite materials in Example 3 and Comparative Example 3 were made into strips by injection molding to test VOC performance. The test results are shown in the following table:

[0082] Test items Test Standards unit P3 D3 benzene GB / T 27630 <![CDATA[μg / m 3 ]]> 48 81 Toluene GB / T 27630 <![CDATA[μg / m 3 ]]> 106 141 Ethylbenzene GB / T 27630 <![CDATA[μg / m 3 ]]> 77 125 Xylene GB / T 27630 <![CDATA[μg / m 3 ]]> 98 156 Styrene GB / T 27630 <![CDATA[μg / m 3 ]]> 45 75 formaldehyde GB / T 27630 <![CDATA[μg / m 3 ]]> 61 91 Acetaldehyde GB / T 27630 <![CDATA[μg / m 3 ]]> 28 48 Acrolein GB / T 27630 <![CDATA[μg / m 3 ]]> 5 18

[0083] It can be seen from the test results in the above table that the VOC performance of the PE composite material of Example 3 is better than that of Comparative Example 3.

[0084] Example 4

[0085] Preparation of VOC improved fillers

[0086] (1) Weigh 325 g of nickel chloride, 175 g of template agent ethylenediamine, 105 g of oxidant hydrogen peroxide, 315 g of sodium hydroxide, and 825 g of deionized water, place in a reaction vessel, react at 38° C. for 6.5 h, filter, wash, and dry to obtain mesoporous hydroxylated nickel oxide;

[0087] (2) 295 g of mesoporous hydroxylated nickel oxide was mixed with 55 g of dimethyl dioctadecyl ammonium bromide, 535 g of anhydrous ethanol, and 925 g of deionized water, placed in a reaction vessel, and reacted at 58° C. for 9 h to obtain a mixed solution;

[0088] (3) The mixed solution is filtered, washed and dried to obtain VOC improved filler M4.

[0089] Preparation of PA6 composite materials

[0090] (1) 99 parts of PA6, 11 parts of VOC improved filler M4, 0.1 parts of antioxidant Irganox 1010, and 0.2 parts of antioxidant Irganox 1330 were weighed and mixed and stirred to obtain a mixture;

[0091] (2) The mixed material obtained in step (1) is extruded and granulated from a twin-screw extruder to obtain a PA6 composite material, which is denoted as P4.

[0092] Among them, the twin-screw extruder includes six temperature zones arranged in sequence, the temperature of the first temperature zone is 210°C, the temperature of the second temperature zone is 260°C, the temperature of the third temperature zone is 260°C, the temperature of the fourth temperature zone is 260°C, the temperature of the fifth temperature zone is 260°C, the temperature of the sixth temperature zone is 260°C, the head temperature of the twin-screw extruder is 260°C, and the screw speed is 320r / min.

[0093] Comparative Example 4

[0094] This comparative example adopts the same implementation as Example 4 to prepare the PA6 composite material, except that the VOC improved filler is replaced by the mesoporous hydroxylated nickel oxide prepared in Example 4; the other steps are the same as Example 4, and the specific steps are as follows:

[0095] (1) 99 parts of PA6, 11 parts of the mesoporous hydroxylated nickel oxide prepared in Example 4, 0.1 parts of antioxidant Irganox 1010, and 0.2 parts of antioxidant Irganox 1330 were weighed and mixed and stirred to obtain a mixture;

[0096] (2) extruding the mixture obtained in step (1) through a twin-screw extruder to form granules, thereby obtaining a PA6 composite material, which is recorded as D4;

[0097] Among them, the twin-screw extruder includes six temperature zones arranged in sequence, the temperature of the first temperature zone is 210°C, the temperature of the second temperature zone is 260°C, the temperature of the third temperature zone is 260°C, the temperature of the fourth temperature zone is 260°C, the temperature of the fifth temperature zone is 260°C, the temperature of the sixth temperature zone is 260°C, the head temperature of the twin-screw extruder is 260°C, and the screw speed is 320r / min.

[0098] The PA6 composite materials prepared in Example 4 and Comparative Example 4 were made into strips by injection molding to test VOC performance. The test results are shown in the following table:

[0099] Test items Test Standards unit P4 D4 benzene GB / T 27630 <![CDATA[μg / m 3 ]]> 39 62 Toluene GB / T 27630 <![CDATA[μg / m 3 ]]> 85 138 Ethylbenzene GB / T 27630 <![CDATA[μg / m 3 ]]> 84 131 Xylene GB / T 27630 <![CDATA[μg / m 3 ]]> 82 151 Styrene GB / T 27630 <![CDATA[μg / m 3 ]]> 40 61 formaldehyde GB / T 27630 <![CDATA[μg / m 3 ]]> 55 71 Acetaldehyde GB / T 27630 <![CDATA[μg / m 3 ]]> 19 26 Acrolein GB / T 27630 <![CDATA[μg / m 3 ]]> 7 11

[0100] It can be seen from the test results in the above table that the VOC performance of the PA6 composite material prepared in Example 4 is better than that of Comparative Example 4.

[0101] Example 5

[0102] Preparation of VOC improved fillers

[0103] (1) Weigh 395 g of nickel chloride, 178 g of template agent ethylenediamine, 111 g of oxidant hydrogen peroxide, 295 g of sodium hydroxide, and 895 g of deionized water, place in a reaction vessel, react at 38° C. for 6 h, filter, wash, and dry to obtain mesoporous hydroxylated nickel oxide;

[0104] (2) 285 g of mesoporous hydroxylated nickel oxide was mixed with 55 g of dimethyl dioctadecyl ammonium bromide, 575 g of anhydrous ethanol, and 915 g of deionized water, placed in a reaction vessel, and reacted at 48° C. for 9.5 h to obtain a mixed solution;

[0105] (3) The mixed solution is filtered, washed and dried to obtain VOC improved filler M5.

[0106] Preparation of PET composite materials

[0107] (1) Weigh 110 parts of PET, 11 parts of VOC improved filler M5, 0.1 parts of antioxidant Irganox 1010, and 0.1 parts of antioxidant Irganox 168 according to weight, mix and stir evenly to obtain a mixture;

[0108] (2) The mixed material obtained in step (1) is extruded and granulated from a twin-screw extruder to obtain a PET composite material, which is denoted as P5.

[0109] Among them, the twin-screw extruder includes six temperature zones arranged in sequence, the temperature of the first temperature zone is 240°C, the temperature of the second temperature zone is 280°C, the temperature of the third temperature zone is 280°C, the temperature of the fourth temperature zone is 280°C, the temperature of the fifth temperature zone is 280°C, the temperature of the sixth temperature zone is 280°C, the head temperature of the twin-screw extruder is 280°C, and the screw speed is 280r / min.

[0110] Comparative Example 5

[0111] This comparative example adopts the same implementation method as Example 5 to prepare the PET composite material, the only difference being that the VOC modified filler is replaced by the mesoporous hydroxylated nickel oxide in Example 5; the other steps are the same as Example 5, and the specific steps are as follows:

[0112] (1) Weigh 110 parts of PET, 11 parts of the mesoporous hydroxylated nickel oxide prepared in Example 5, 0.1 parts of antioxidant Irganox 1010, and 0.1 parts of antioxidant Irganox 168, and mix and stir to obtain a mixture;

[0113] (2) extruding the mixture obtained in step (1) through a twin-screw extruder to form granules, thereby obtaining a PET composite material, which is recorded as D5;

[0114] Among them, the twin-screw extruder includes six temperature zones arranged in sequence, the temperature of the first temperature zone is 240°C, the temperature of the second temperature zone is 280°C, the temperature of the third temperature zone is 280°C, the temperature of the fourth temperature zone is 280°C, the temperature of the fifth temperature zone is 280°C, the temperature of the sixth temperature zone is 280°C, the head temperature of the twin-screw extruder is 280°C, and the screw speed is 280r / min.

[0115] The PET composite materials obtained in Example 5 and Comparative Example 5 were made into strips by injection molding to test VOC performance. The test results are shown in the following table:

[0116] Test items Test Standards unit P5 D5 benzene GB / T 27630 <![CDATA[μg / m 3 ]]> 45 78 Toluene GB / T 27630 <![CDATA[μg / m 3 ]]> 69 108 Ethylbenzene GB / T 27630 <![CDATA[μg / m 3 ]]> 77 139 Xylene GB / T 27630 <![CDATA[μg / m 3 ]]> 91 148 Styrene GB / T 27630 <![CDATA[μg / m 3 ]]> 32 59 formaldehyde GB / T 27630 <![CDATA[μg / m 3 ]]> 42 68 Acetaldehyde GB / T 27630 <![CDATA[μg / m 3 ]]> 23 41 Acrolein GB / T 27630 <![CDATA[μg / m 3 ]]> 8 15

[0117] It can be seen from the test results in the above table that the VOC performance of the PET composite material prepared in Example 5 is better than that of Comparative Example 5.

[0118] It can be seen from the above examples and comparative examples that adding the VOC improved filler prepared in the present application to a thermoplastic resin composite material can significantly improve the VOC performance of the composite material and expand the application scope of the thermoplastic resin composite material.

[0119] The technical features of the above-described embodiments may be arbitrarily combined. To make the description concise, not all possible combinations of the technical features in the above-described embodiments are described. However, as long as there is no contradiction in the combination of these technical features, they should be considered to be within the scope of this specification.

[0120] The above-mentioned embodiments only express several implementation methods of the present invention, and the descriptions thereof are relatively specific and detailed, but they cannot be understood as limiting the scope of the invention patent. It should be pointed out that, for ordinary technicians in this field, several variations and improvements can be made without departing from the concept of the present invention, and these all belong to the protection scope of the present invention. Therefore, the protection scope of the patent of the present invention shall be subject to the attached claims.

Claims

1. A method for preparing a VOC improved filler, characterized in that: The following steps are involved: Mix nickel chloride, template, oxidant, sodium hydroxide and deionized water, and react at 30-50° C. for 5-7 hours to prepare mesoporous hydroxylated nickel oxide; The mesoporous hydroxylated nickel oxide is mixed with dimethyl dioctadecyl ammonium bromide, anhydrous ethanol and deionized water, and reacted at 40-60° C. for 6-10 hours to obtain a mixed solution; The mixed solution is filtered, washed and dried to obtain a VOC improved filler, namely a mesoporous hydroxylated nickel oxide filler modified by dimethyl dioctadecyl ammonium bromide.

2. The method for preparing the VOC improved filler according to claim 1, characterized in that: The template agent is ethylenediamine.

3. The method for preparing the VOC improved filler according to claim 1, characterized in that: The oxidant is hydrogen peroxide.

4. The method for preparing the VOC improved filler according to claim 1, characterized in that: In the step of obtaining mesoporous hydroxylated nickel oxide, the mass ratio of nickel chloride, template, oxidant, sodium hydroxide and deionized water is (30-40): (16-18): (8-12): (28-32): (70-90).

5. The method for preparing the VOC improved filler according to claim 1, characterized in that: In the step of obtaining a mixed solution, the mass ratio of the mesoporous hydroxylated nickel oxide, dimethyl dioctadecyl ammonium bromide, anhydrous ethanol and deionized water is (28-30):(4-6):(50-60):(80-100).

6. A VOC improved filler, characterized in that: The method is prepared according to any one of claims 1 to 5.

7. Use of the VOC improving filler as claimed in claim 6 in thermoplastic resin composite materials.

8. A thermoplastic resin composite material, characterized in that: It is prepared from 95 to 115 parts of a thermoplastic resin, 8 to 12 parts of the VOC-improving filler as claimed in claim 6, and 0.1 to 0.5 parts of an antioxidant according to parts by weight; Preferably, the thermoplastic resin is selected from one of polyethylene, polypropylene, polyethylene terephthalate, polybutylene terephthalate, and polyamide 6; Preferably, the antioxidant is selected from at least one of antioxidant 168, antioxidant 1010, and antioxidant 1330.

9. A method for preparing a thermoplastic resin composite material as claimed in claim 8, characterized in that: The following steps are involved: Weigh 95-115 parts of thermoplastic resin, 8-12 parts of VOC improved filler, and 0.1-0.5 parts of antioxidant according to the weight ratio, mix and stir evenly to obtain a mixture; The mixed material is melt-extruded and granulated to obtain a thermoplastic resin composite material.